Floods in a changing climate, Risk management - Simonović, Slobodan P. (Cambridge University Press, 2012)
"Flood risk management is presented in this book as a framework for identifying, assessing and prioritizing climate-related risks and developing appropriate adaptation responses. Rigorous assessment is employed to determine the available probabilistic and fuzzy set-based analytic tools, when each is appropriate and how to apply them to practical problems. Academic researchers in the fields of hydrology, climate change, environmental science and policy and risk assessment, and professionals and policy-makers working in hazard mitigation, water resources engineering and environmental economics, will find this an invaluable resource. This volume is the fourth in a collection of four books on flood disaster management theory and practice within the context of anthropogenic climate change. The others are: Floods in a Changing Climate: Extreme Precipitation by Ramesh Teegavarapu, Floods in a Changing Climate: Hydrological Modelling by P. P. Mujumdar and D. Nagesh Kumar and Floods in a Changing Climate: Inundation Modelling by Giuliano Di Baldassarre"--